Date Seed Oil Possesses a Protective Effect Against Paracetamol-induced Hepatotoxicity - Heba M Eltahir (Zagazig Journal of Pharmaceutical Sciences)
Background: Liver is a vital organ performing major metabolic and detoxification reactions, which makes it very liable to damage and injury by a wide range of drugs and xenobiotics. Paracetamol (PCM) is an over-the-counter analgesic that is considered to be safe at therapeutic doses; however, getting beyond the therapeutic doses can induce acute hepatic and renal injury. PCM-induced liver injury is a commonly used model for investigating the hepatoprotective and therapeutic significance of drugs and natural products. Date seed oil (DSO) is extracted from the fruit seed of date palm (Phoenix Dactylifera L). Aim: the current study aims at investigating the hepatoprotective potential of DSO in PCM-induced hepatotoxicity. Methods: Swiss albino rats were assigned to three groups; healthy control (a daily oral dose of saline, 14 days), PCM-treated (300mg/kg, a single oral dose after 14 days of a daily oral saline dose) and DSO-PCM-treated (1ml oil/kg, daily oral dose for 14 days, followed by a single PCM dose). Animals were sacrificed and blood and liver tissue were collected for biochemical and histological evaluation. Results: PCM treatment induced a significant increase in liver enzymes aspartate transaminase, alanine transaminase, lactate dehydrogenase, and alkaline phosphatase, in addition to total bilirubin and cholesterol levels. It significantly decreased total proteins, albumin and blood glucose levels and negatively altered liver histology. DSO treatment protected against PCM-induced changes in liver enzymes, and biochemical parameters. It also protected liver tissue from histopathological changes. Conclusion: DSO has a potential hepatoprotective effect against PCM-induced acute liver injury.